2004
DOI: 10.1128/aac.48.4.1295-1299.2004
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Plasmid-Mediated Quinolone Resistance Associated with the qnr Gene in Klebsiella pneumoniae Clinical Isolates in the United States

Abstract: Although quinolone resistance commonly results from chromosomal mutation, recent studies indicate that such resistance can also be transferred on plasmids carrying the gene responsible, qnr. One hundred ten ciprofloxacin-resistant clinical isolates of Klebsiella pneumoniae and Escherichia coli from the United States were screened for the qnr gene by PCR and Southern hybridization of plasmid DNA. Conjugation experiments were done with azide-resistant E. coli J53 as the recipient and selection with azide and sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
175
0
12

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(194 citation statements)
references
References 18 publications
5
175
0
12
Order By: Relevance
“…This rate of qnr prevalence was consistent with some studies carried out in Taiwan and the USA (15,16). Prevalence of qnr in the present study was also higher than that shown in other areas in Brazil (2.3%), Singapore (5.2%) and the USA (11.1%) [12,13,17]. In contrast, it was much lower than the prevalence of qnr genes detected in Malaysia (48.9%) and China (65.5%) [14,19].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This rate of qnr prevalence was consistent with some studies carried out in Taiwan and the USA (15,16). Prevalence of qnr in the present study was also higher than that shown in other areas in Brazil (2.3%), Singapore (5.2%) and the USA (11.1%) [12,13,17]. In contrast, it was much lower than the prevalence of qnr genes detected in Malaysia (48.9%) and China (65.5%) [14,19].…”
Section: Discussionsupporting
confidence: 80%
“…Although the qnr gene indicates a low level of resistance to quinolones, its attendance aids the selection of chromosomal mutations, facilitating increased resistance in the host strain [9][10][11]. Frequency of qnr genes PMQR associated with the qnr genes in different human clinical enterobacterial isolates was determined first in the USA in 1994 using a K. pneumoniae isolate (later termed qnrA1) [9], which was then widely reported worldwide [12][13][14][15][16][17][18][19]. However, no study has been done on prevalence of qnr genes among enterobacterial clinical isolates in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to quinolones is mainly due to mutations in the quinoloneresistance determining region of DNA gyrase and topoisomerase IV (19). In Japan, there are no reports about plasmid-mediated quinolone resistance as reported in other countries (5,13,23,24). Hence, it is likely that the occurrence of resistance against nalidixic acid is not linked to the prevalence of multi-antimicrobial resistance.…”
Section: Discussionmentioning
confidence: 97%
“…Conjugation was carried on the isolates; according to Wang et al 31 and Yutaka et al 36 with Ps. aeruginosa strain ATCC 10145 used as the recipient mating strains were incubated at 37°C for 18 hours without shaking.…”
Section: Conjugation and Plasmids Profilesmentioning
confidence: 99%